Islamic Religious Coping, Partner Support and Parenting Stress On Mothers Who Accompany Their Children Study From Home in a Covid-19 Pandemic Situation - Rahma Kusuma Fitri; Fuad Nashori (Program Studi Psikologi Islam, Fakultas Psikologi, Universitas Islam Negeri Raden Fatah Palembang, 2021)
One of the impacts of the COVID-19 pandemic on the education and family sector is that children are required to study from home (SFH) or online. This condition makes the burden of a mother's responsibility increase because she has to be both a mother and a teacher for her children, where these demands cause mothers to experience parenting stress. This study aims to determine how big the contribution of Islamic religious coping variables and partner support to parenting stress. This study used quantitative research methods with a three-variable correlation research design. The research respondents were 319 mothers in Indonesia with an age range between 26 and 51 years old. The measuring instrument used is Islamic religious coping short-form (IRCS) Raiya (2008), Receipt of Spousal Support Scale (RSSS) from Dorio (2010), and the Parenting Stress Scale (PSS) from Berry and Jones (1995). The research data were analyzed using the SPSS 26 statistical analysis program with multiple linear regression test techniques to answer the research hypothesis. The results showed that there was a significant negative contribution of Islamic religious coping and partner support to parenting stress for mothers who accompanied SFH children in the COVID-19 pandemic situation.